2011
DOI: 10.1063/1.3558988
|View full text |Cite
|
Sign up to set email alerts
|

Angular and energy distribution of Sn ion debris ejected from a laser-produced plasma source, for laser power densities in the range suitable for extreme ultraviolet lithography

Abstract: In this paper, experimental results are presented for the spatial and energy distributions of charge-discriminated Sn ions ejected from laser-produced plasmas. The plasmas were formed on solid, planar Sn targets, irradiated with a Nd:YAG laser. Ions were investigated using a calibrated electrostatic sector analyzer, scanning an energy-to-charge ratio range of 0.22 to 2.2 keV/e for emission angles between 20 and 80 degrees relative to target normal. Results were obtained for three laser power densities, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…5 The distribution of the ions from the slab target shows a similar decay with the angle for all of the measured ion species. Charge states up to Sn 5þ are found in the slab target results, as the condition was in high vacuum.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…5 The distribution of the ions from the slab target shows a similar decay with the angle for all of the measured ion species. Charge states up to Sn 5þ are found in the slab target results, as the condition was in high vacuum.…”
Section: Discussionmentioning
confidence: 78%
“…The angular and kinetic energy distributions of ions from LPPs generated in high vacuum were extensively studied for slab targets of tin, 5 and for other materials. [6][7][8][9][10] The effects of the wavelength on the plasma dynamics from tin slab targets were mainly studied with tin slab targets mainly comparing Nd:YAG and CO 2 lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the laser pulse width used for excitation, the ion fluence increased with increasing laser energy. O'Connor et al 23 noticed similar effects at a fixed laser width and their studies showed both the number and the energy of ions increased with applied laser energy.…”
Section: B Fc Ion Analysismentioning
confidence: 71%
“…22 It was also shown that LPPs exhibit preferential emission close to target normal; the energy of the ions emitted close to the target normal were also higher than that of ions emitted at larger angles. 23 Higashiguchi et al 24 demonstrated suppression of suprathermal ions from a colloidal microjet target plasma containing tin-dioxide (SnO 2 ) nanoparticles irradiated by double laser pulses. As a result, the peak energy of the singly ionized tin ions was reduced from 9 to 3 keV.…”
mentioning
confidence: 98%
“…The nanowire is illuminated by a TM polarized laser pulse at wavelength λ = 1050 nm of complex permittivity ϵ r (TiO 2 ) 1050 = 5.4600 + j 0.00148 with a power density per area units P S = 1.75 × 10 12  W/m 2 [24, 25]. The materials of the system are considered isotropic and homogeneous.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%